Congruence of Gluing of Lattices and Gluing of Congruence Lattices - R.Ratha Jeyalakshmi (International Journal of Advanced Science and Technology, 2020)
In this paper we give an affirmative answer to the problem “Are there lattice construction  for finite lattices A and B